DIFFERENT ASPECTS OF ENGLISH IDIOMS - Rzaeva, R.K.; Eshimbetova, N. (SCIENCE and SOCIETY, 2017)
The article deals with the characteristic features of English idioms. It is emphasized that idioms reflect the culture, traditions and customs of the people, that’s why it is necessary for learners to have sociocultural and intercultural competence to understand them better. The knowledge of idioms and their use in speech makes it more expressive, emotional and persuading, it also promotes to enriching the English vocabulary of learners.